The Impact of Nutrition and Exercise on Kidney Health: How to Prevent Kidney Stones? - Łojewska, Julia Natalia; Rosińska, Kamila; Bochenek, Oliwia; Koper, Mateusz; Janicka, Ewelina Justyna; Perko , Agnieszka; Rosiński, Mateusz; Niedźwiedzka, Monika (Quality in Sport, 2024)
Introduction Kidney stone disease, characterized by the formation of calculi in the kidneys, is becoming an increasingly common urinary tract disorder in developed countries. Although kidney stone disease may be caused by metabolic disorders, anatomical, functional, and genetic factors, diet plays a crucial role in its formation. Changing dietary habits has become a primary tool in the treatment and prevention of kidney stone disease. Objective The aim of this study is to present research on the impact of diet and its individual components on the risk of kidney stone formation. Special attention is given to the role of vitamins, minerals, and dietary habits in the pathogenesis and prevention of this condition. Materials and Methods The study involves a review of the scientific literature, considering research published in reputable medical and scientific journals regarding the impact of diet on the risk of kidney stones, focusing on key dietary components such as calcium, magnesium, sodium, vitamins C and D, as well as the role of physical activity and proper hydration. Conclusions A balanced diet, proper hydration and maintaining a healthy body weight are fundamental elements in preventing of kidney stone disease. Adequate hydration is crucial; high fluid intake, especially water, dilutes urine and reduces the concentration of lithogenic substances.Calcium and magnesium intake are particularly important as they influence the absorption and excretion of oxalates, and excessive supplementation with vitamins C and D should be avoided. A diet rich in fruits and vegetables, and the limitation of animal protein and salt, can significantly reduce the risk of kidney stone formation. Ultimately, dietary changes and lifestyle modifications, including weight control and physical activity, play a crucial role in preventing kidney stone disease. However, further research is needed to develop effective dietary guidelines tailored to the individual needs of patients.